2003
DOI: 10.1002/glia.10259
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine, chemokine and growth factor gene profiling of cultured human astrocytes after exposure to proinflammatory stimuli

Abstract: Astrocytes play key roles in CNS development, inflammation, and repair by producing a wide variety of cytokines, chemokines, and growth factors. Understanding the regulation of this network is important for a full understanding of astrocyte functioning. In this study, expression levels of 268 genes encoding cytokines, chemokines, growth factors, and their receptors were established in cultured human adult astrocytes using cDNA arrays. Also, changes in this gene profile were determined following stimulation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
131
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(144 citation statements)
references
References 59 publications
9
131
1
2
Order By: Relevance
“…22 Indeed, not only was IL-17 mRNA detected in an earlier study in astrocytes cultured from adult donors in a gene array analysis, 37,42 but it was also up-regulated after treatment with tumor necrosis factor-␣ or IL-1␤, but not, interestingly, with interferon-␥. 43 Again, this agrees with the known polarization of T H 17 cells by such proinflammatory cytokines as IL-6, tumor necrosis factor-␣, and IL-1␤.…”
Section: Discussionsupporting
confidence: 84%
“…22 Indeed, not only was IL-17 mRNA detected in an earlier study in astrocytes cultured from adult donors in a gene array analysis, 37,42 but it was also up-regulated after treatment with tumor necrosis factor-␣ or IL-1␤, but not, interestingly, with interferon-␥. 43 Again, this agrees with the known polarization of T H 17 cells by such proinflammatory cytokines as IL-6, tumor necrosis factor-␣, and IL-1␤.…”
Section: Discussionsupporting
confidence: 84%
“…The CC chemokines MCP-1 and RANTES, which are major attractants for monocyte/macrophage entry into the CNS and key initiators of proinflammatory cascades (Luo et al, 2002a), have been found in the brain tissue and cerebrospinal fluid of patients with HIV-1 encephalitis and AIDS dementia complex (Kelder et al, 1998;McManus et al, 2000). Although the cytokine array is sensitive and can reportedly detect protein levels as low as 4 pg/ml (compared to 40 pg/ml with ELISA), we did not see increases in TNF-α release at 4 or 12 h. Increases in TNF-α were anticipated because Tat has been previously reported to increase TNF-α expression in astrocytes (Chen et al, 1997) and TNF-α can induce the expression of IL-6 (Norris et al, 1994), MCP-1 (Oh et al, 1999;Luo et al, 2003), and RANTES (Oh et al, 1999;Meeuwsen et al, 2003) in human and/or mouse astrocytes. Importantly, we found large relative increases in TNF-α mRNA levels at 30 min and declining levels thereafter in response to Tat 1-72 exposure.…”
Section: Discussionmentioning
confidence: 47%
“…Nevertheless, G-CSF treatment significantly increased the number of intrinsic Iba-1-positive microglia. While several studies examined the relationship between astrocytes and G-CSF (Meeuwsen et al, 2003), to our knowledge, our study is the first that reports G-CSF-induced microglial activation. Microglia/macrophages are considered the major source of inflammatory cytokines in the ischemic brain (Gregersen et al, 2000;Lambertsen et al, 2002).…”
Section: Discussionmentioning
confidence: 89%